APOBEC mutagenesis is tightly linked to the immune landscape and immunotherapy biomarkers in head and neck squamous cell carcinoma. (September 2019) - Faden, Daniel L.; Ding, Fei; Lin, Yan; Zhai, Shuyan; Kuo, Fengshen; Chan, Timothy A.; Morris, Luc G.; Ferris, Robert L.
Highlights: IFNy levels in HNSCC are elevated above other cancer types with high APOBEC mutational burden. Immune cell density and scores of immune activation are correlated with APOBEC mutational burden. Mutation-induced neoantigens may be driving force for APOBEC mutations in HNSCC. Germline APOBEC polymorphism prevalence differs by race and may result in more APOBEC mutations. Abstract: HNSCC is an immunologically active tumor with high levels of immune cell infiltration, high mutational burden and a subset of patients who respond to immunotherapy. One of the primary sources of mutations in HNSCC is the cytidine deaminase APOBEC3, which is a known participant in innate immunity. Why particular HNSCCs have higher rates of APOBEC mutations and how these mutations relate to the immune microenvironment remains unknown. Utilizing whole exome and RNA-Seq datasets from TCGA HNSCCs we annotated APOBEC mutations, immune cell populations, activating and end effectors of immunity and neoantigens in order to interrogate the relationship between APOBEC mutations and the immune landscape. Immune cell populations and composite scores of immune activation were tightly associated with APOBEC mutational burden (p = 0.04–1.17e-5). HNSCC had the highest levels of IFNy across cancer types with high APOBEC mutational burden, with the highest IFNy scores in HPV mediated HNSCC. Tumor specific neoantigens were significantly correlated with APOBEC mutational burden while other sources of neoantigens were not (0.53 [0.24, 0.76] p = 8e-5). The presence of a germline APOBEC polymorphism was more prevalent in non-white, non-black patients and within this group, patients with the polymorphism had higher APOBEC mutational burden (p = 0.002). APOBEC mutations are tightly linked to immune activation and infiltration in HNSCC. Multiple mechanisms may exist within HNSCC leading to APOBEC mutations including immune upregulation in response to neoantigens and viral infection, via induction of IFNy. These mechanisms may be additive and not mutually exclusive, which could explain higher levels of APOBEC mutations in HPV mediated HNSCC.